A novel approach for addressing diseases not yielding to effective vaccination? Immunization by replication-competent controlled virus - Voellmy, Richard; Bloom, David C; Vilaboa, Nuria (Expert review of vaccines, 2015)
Vaccination involves inoculation of a subject with a disabled disease-causing microbe or parts thereof. While vaccination has been highly successful, we still lack sufficiently effective vaccines for important infectious diseases. We propose that a more complete immune response than that elicited from a vaccine may be obtained from immunization with a disease-causing virus modified to subject replication-essential genes to the control of a gene switch activated by non-lethal heat in the presence of a drug-like compound. Upon inoculation, strictly localized replication of the virus would be triggered by a heat dose administered to the inoculation site. Activated virus would transiently replicate with an efficiency approaching that of the disease-causing virus and express all viral antigens. It may also vector heterologous antigens or control co-infecting microbes.